2013
DOI: 10.1186/1742-2094-10-35
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages in inflammatory multiple sclerosis lesions have an intermediate activation status

Abstract: BackgroundMacrophages play a dual role in multiple sclerosis (MS) pathology. They can exert neuroprotective and growth promoting effects but also contribute to tissue damage by production of inflammatory mediators. The effector function of macrophages is determined by the way they are activated. Stimulation of monocyte-derived macrophages in vitro with interferon-γ and lipopolysaccharide results in classically activated (CA/M1) macrophages, and activation with interleukin 4 induces alternatively activated (AA/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
371
3
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 420 publications
(403 citation statements)
references
References 65 publications
24
371
3
5
Order By: Relevance
“…25; and hence paramagnetic, Figure 8) to antiinflammatory/repair-promoting myeloid cells at the lesion edge, but also possibly to persistent oxidative stress. Notably, the identities and functional phenotypes of macrophages have been shown to be extremely dynamic and responsive to varying environmental signals, and an intermediate activation status is often detected (26). Thus, we have chosen to use the broader terms "inflammatory" and "repair-promoting" (antiinflammatory) in lieu of M1 and M2 polarization status (27).…”
Section: Discussionmentioning
confidence: 99%
“…25; and hence paramagnetic, Figure 8) to antiinflammatory/repair-promoting myeloid cells at the lesion edge, but also possibly to persistent oxidative stress. Notably, the identities and functional phenotypes of macrophages have been shown to be extremely dynamic and responsive to varying environmental signals, and an intermediate activation status is often detected (26). Thus, we have chosen to use the broader terms "inflammatory" and "repair-promoting" (antiinflammatory) in lieu of M1 and M2 polarization status (27).…”
Section: Discussionmentioning
confidence: 99%
“…Published data have shown the presence of Ma with intermediate phenotype in human CNS (28) and in murine heart tissue after acute myocardial infarction (8) and after a Th2 immunologic challenge (7). In the current study, we found that a subset with a mixed phenotype was the main heart population during all time points studied.…”
Section: Discussionmentioning
confidence: 99%
“…Extrapolating findings from in vitro studies to disease in vivo is more problematic. For example, intermediate phenotypes are observed in diseased tissues, 21 indicating that an overlapping spectrum is more realistic and that such quantitative and qualitative differences will occur in the spectrum of neurodegenerative disorders.…”
Section: Towards Therapeutic Modulation Of Microgliamentioning
confidence: 99%